2015
DOI: 10.1111/risa.12440
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Measles Transmission in the North American Amish and Options for Outbreak Response

Abstract: Measles outbreaks in the United States continue to occur in subpopulations with sufficient numbers of undervaccinated individuals, with a 2014 outbreak in Amish communities in Ohio pushing the annual cases to the highest national number reported in the last 20 years. We adapted an individual-based model developed to explore potential poliovirus transmission in the North American Amish to characterize a 1988 measles outbreak in the Pennsylvania Amish and the 2014 outbreak in the Ohio Amish. We explored the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Through monitoring of measles communicability during this outbreak, we showed that containment efforts probably contributed to reducing the spread of measles, and we demonstrated that launching comprehensive and timely public health responses can help avert the occurrence of large outbreaks in underimmunized populations. These findings corroborate previous results from an individual-based model also showing the potential for measles spread to other North American Amish communities in the absence of outbreak responses (6). As containment measures started to get under way, we found an approximately 4-fold reduction in transmissibility (R t declined from 4.6 to 1) over the course of 2 weeks and subsequent maintenance of R t below unity as control measures continued.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Through monitoring of measles communicability during this outbreak, we showed that containment efforts probably contributed to reducing the spread of measles, and we demonstrated that launching comprehensive and timely public health responses can help avert the occurrence of large outbreaks in underimmunized populations. These findings corroborate previous results from an individual-based model also showing the potential for measles spread to other North American Amish communities in the absence of outbreak responses (6). As containment measures started to get under way, we found an approximately 4-fold reduction in transmissibility (R t declined from 4.6 to 1) over the course of 2 weeks and subsequent maintenance of R t below unity as control measures continued.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the model also assumes a homogenous effect of vaccination efforts, which may underestimate their impact. In addition, final outbreak sizes and the impact of the interventions depend on the estimated population at risk, and we did not measure the impact of the response in limiting spread to other Amish communities, including those outside Ohio (6). Because of these caveats, the trajectories we present should not be viewed as exact projections, but they characterize probable trends in transmissibility and in the potential for control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a) and rubella (Fig b). Modeling the incidence and the die out of transmission required that we include an undervaccinated subpopulation, which in the United States includes some communities that do not obtain immunization for religious reasons (e.g., the Amish) and some families who intentionally remain undervaccinated . Given aggressive outbreak response in the United States, we included ORI starting in 1967 assuming that outbreaks led to the immunization of some previously unvaccinated individuals only.…”
Section: Resultsmentioning
confidence: 99%
“…The model includes regular importations into the general population, which may lead to transmission in undervaccinated subpopulations. However, for importation events that involved known importations into an undervaccinated subpopulation we modeled the importation directly into the undervaccinated subpopulation. The model yields estimates of rubella cases that correspond to approximately 24,000 pregnancy outcomes adversely affected (e.g., pregnancy terminations due to rubella, fetal deaths, infant mortality, and CRS cases) due to the maternal rubella infection associated with the large outbreak that peaked in 1964, similar to prior estimates .…”
Section: Resultsmentioning
confidence: 99%